The Hobbit or there and back again - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (HarperCollins, 2006)
Smaug certainly looked fast asleep, when Bilbo peeped once more from the entrance. He was just about to step out onto the floor when he caught a sudden thin and piercing ray of red from under the drooping lid of Smaug's left eye. He was only pretending to sleep!